A relative approach to the validation of surrogate measures of safety. (October 2021) - Johnsson, Carl; Laureshyn, Aliaksei; Dágostino, Carmelo
Highlights: Relative validation of minimum time to collision and post encroachment time. Focus on interactions between motor vehicles and vulnerable road users. Observational study at 6 signalized intersections in Denmark and the Netherlands. Event-based exposure shows a strong correlation to both indicators. Minimum time to collision outperforms post encroachment time. Abstract: Surrogate measures of safety (SMoS) are meant to be an alternative/complement to crash data that enables a proactive approach to traffic safety. Validity is a fundamental property of SMoS that describes how well they reflect the quality of interest – traffic safety. However, typical validation studies are extremely resource demanding. Therefore, the aim of this study was to explore a relative approach to validity that uses fewer resources and does not rely on crash records from the observed locations. The core idea of a relative approach to the validation of SMoS is that while SMoS might not accurately estimate the expected number of crashes, they still work well for comparisons between different sites or between conditions at the same site. Based on this concept, we propose a method in which a ground truth based on literature can be used as a baseline that can then be compared to the safety analysis of an SMoS study. Using the proposed method, a case study of six intersections in northern Europe was conducted, focusing on bicycle infrastructure. The results indicate that the minimum time-to-collision indicator is in line with the ground truth, whereas the post-encroachment time indicator is not.